0605 Correspondence between the ARES Unicorder and ARES Questionnaire in the Evaluation of Obstructive Sleep Apnea among Cognitively Normal Elderly Adults. (27th April 2018) - Rogers, A; Pamer, G; Seixas, A; Zizi, S; Jean-Louis, G; Osorio, R
Abstract: Introduction: Obstructive sleep apnea (OSA) is a common sleep-breathing disorder that affects 3–7% of adult men and 2–5% of adult women in the U.S. population. Home recording for detection of OSA has become increasingly more convenient to evaluate OSA severity. The purpose of this study was to assess the correspondence between the ARES Unicorder and the ARES questionnaire in evaluating OSA among cognitively normal elderly. Methods: Data was derived from a 2-year prospective longitudinal study that sampled community-dwelling healthy cognitively normal elderly. Participants' age ranged from 55 to 90 years. OSA was evaluated using ARES Unicorder (Watermark) during a 2-night period during the latter end of the study; the ARES questionnaire was administered at baseline. To assess the presence of any cognitive abnormalities, the mini-mental state examination was administered; a score of 24–30 indicated no cognitive impairment. Results: Of the 87 participants, 83 provided complete data for the present analysis. Of those, 70 had low OSA risk (ARES score < 4); 13 had a score ≥ 4). Sixty-eight participants completed ARES Unicorder (30 with a score < 5, 38 with a score ≥ 5). Chi square analysis revealed a significant association between self-reported ARES and Unicorder scores ( p -value = 0.001). To assess the true positive rate or sensitivity of ARES Unicorder, an ROC curve was constructed, revealing an AUC of .541, but it was not statistically significant. Of interest, when we considered an ARES questionnaire score > 4, ARES Unicorder showed a statistical significance ( p -value = 0.001). Conclusion: Individuals who score high on the low end of an ARES questionnaire should be further evaluated for OSA using the ARES Unicorder. Overall, discrepancy between self-reported ARES and ARES Unicorder scores require further investigation. We found that self-reported OSA risk tended to be lower, compared to results of the ARES Unicorder. This suggests that individuals might be underreporting OSA symptoms or the ARES questionnaire may not be very sensitive in capturing OSA risk. Support (If Any): R01HL118624-01; CTSI UL1TR000038 and K07AG052685.